PROFITABILITAS, LEVERAGE, NET WORKING CAPITAL, DAN PENGARUHNYA TERHADAP CASH HOLDINGS - Henny Wirianata; Viriany Viriany; Christy Angelia (PROSIDING SERINA, 2021)
Since the Covid-19 pandemic, companies have been encouraged to have adequate amounts of cash in hand as an embodiment of precautionary motives. The company must have adequate cash in hand as a reserve fund in dealing with unexpected crises. This research was conducted to determine the effect of financial performance consisting of profitability, leverage, and net working capital on cash holdings. The data in the study is secondary data from the financial statements of manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the research period 2017-2019. The data was taken by purposive random sampling. The data in the study was processed using Eviews 10. Data analysis uses regression analysis of panel data. Profitability proxied with ROA has a positive but insignificant effect. Leverage proxied with DAR has a negative effect but has no significant effect on cash holdings. Net working capital can significantly lower the amount of cash on hand. Together the levels of profitability, leverage, and net working capital significantly affect the amount of cash on hand.